The Effect of Telecounseling on the Anxiety of Pregnant Women during the COVID-19 Pandemic at the Belusuh Health Center in West Kutai in 2022 - Juliati; Nina Mardiana; Gajali Rahman (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of telecounseling on the anxiety of pregnant women during the COVID-19 pandemic. This type of research is a quantitative research with a quasy experimental research design with a one group pre-post test design. The population in this study were pregnant women in the working area of ​​the Belusuh Health Center, totaling 57 people. The sampling technique used was purposive sampling with a total sample of 14 people. Data analysis technique using the Wilcoxon test. Based on the research results obtained, it can be concluded that there is an effect of telecounseling on the anxiety of pregnant women during the COVID-19 pandemic at the Belusuh Kutai Barat Health Center as evidenced by the results of the statistical test p-value 0.001 (< α = 0.05). After attending counseling for pregnant women, they are able to express disturbing feelings and feel relieved and relaxed.